Quality of life after stenting for chronic iliocaval obstruction. (July 2022) - Tosenovsky, Patrik; Vlaskovsky, Philip
Background: Iliocaval stenting is widely used for treatment of symptomatic iliocaval obstruction. The aim of our study was to compare quality of life before and after iliocaval stenting. Method: Prospectively collected data using CIVIQ20 questionnaire, Venous Clinical Severity Score (rVCSS) and Villalta-Prandoni score (VP) of patients following iliocaval stenting for non-thrombotic and post-thrombotic venous obstruction were analysed. Result: One hundred and one limbs (87 patients) were stented between May 2017 and May 2019. Baseline CIVIQ20 median value was 50 (34–66); 1 month after surgery CIVIQ20 value was 36 (26–58) and the scores then remained steady for the rest of the first year. Both rVCSS and VP scores decrease by 3.09 (95% CI: 2.39, 3.89; p < .001) and 5.21 (95% CI: 4.14, 6.48; p < .001) units, respectively, throughout the first year. Conclusion: Quality of life of patients with iliocaval obstruction significantly improves after successful percutaneous reconstruction. Severity of symptoms measured by rVCSS and VP scores decreases.